Love suffereth long: investigating the nexus between brand love and price tolerance in the banking industry - David Amani; Mariam Said Kapipi (Cogent Business & Management)
While positive word of mouth has been extensively studied as a driver of attitudinal loyalty, comparatively less attention has been devoted to exploring price tolerance. This study tests the role of brand love on price tolerance through switching barriers in the banking industry. The study employed a cross-sectional design with a quantitative approach to gather data from 408 customers. The collected data was then analyzed using structured equation modeling. The results indicate that the dimensions of brand love, specifically brand intimacy, brand commitment, and brand passion, have an impact on price tolerance through the mediation of switching barriers. The results suggest that when customers develop a sense of intimacy, commitment, and passion demonstrating their love for the bank brand they are more likely to intend to sustain their relationship with the bank. Similarly, customers who intend to maintain their relationship with the bank are more likely to tolerate various changes implemented by the bank, including those related to service charges or costs. The study recommends that commercial banks provide immersive experiences to customers as a means of enhancing their brand love.